THE ROLE OF ORGANIZATIONAL CULTURE AND KNOWLEDGE SHARING ON EMPLOYEE PRODUCTIVITY - Abdul Rohim (Proceeding International Conference on Digital Education and Social Science, 2022)
This research, conducted at Jombang Education and Culture Service, aims to test the role of organizational culture and knowledge sharing on employee productivity. This research is a descriptive-quantitative approach. Data collection used a survey. The sample in this study was 77 people consisting of echelon II.b to IV.a officials and staff with civil servant status. The analysis technique used Partial Least Square with SmartPLS 3.0 application. The results showed that the clan culture employees most strongly felt were the organizational culture. The interaction between organizational culture and knowledge sharing had a significant and positive effect, and knowledge sharing had a positive and significant effect on employee productivity. Knowledge sharing was proven to moderate the relationship between organizational culture and employee productivity, but organizational culture directly and significantly affected employee productivity.